Reviewing activities for International Journals (for period 2018-2020) - Fyndanis, Valantis (My University, 2026)
I acted as ad-hoc reviewer for the following journals:AphasiologyLanguage, Cognition and NeuroscienceJournal of Communication DisordersFrontiers in CommunicationClinical Linguistics and PhoneticsJournal of Alzheimer’s DiseaseJournal of Neurolinguistics